The Relationship between Job Stress Risk Factors andWorkplace Well-Being with the Moderating Effects of JobBurnout: A Study of Substitute Educators for Early ChildhoodEducation in Taiwan - Kao, Chia-Lin; Chang, Wei-Wen (European Journal of Multidisciplinary Studies, 2022)
Nowadays, the employees’ well-being has been an increasingly relevant and necessary consideration in the workplace. However, little attention has been paid to the well-being of substitute educators in preschool. Working in early childhood education is stressful, and certain types of stress negatively affect physical and mental health. The participants in this study are substitute educators for early education in Taiwan. The substitute educators of preschools in the working environment are not stable and peaceful. In addition to engaging in the same teaching programs as the formal teachers, substitute teachers have to work for additional administrative assignments in schools. Furthermore, they were often viewed as the marginal role in the workplace, enduring discrimination from the unfriendly organization. Their working environment is full of pressure, contradictions, and conflicts. Substitute teachers often endure negative emotions and need to suppress their true feelings. Thus, the aim of this research is to examine the relationship among preschool substitute teachers’ well-being (Y), job stress risk factors (X), and burnout (Mo). Data was collected from a survey of 102 substitute educators at both public and private preschools in Taiwan. Among the six stress risk factors, good control, managerial support, colleague support, roles, and change were positively related to well-being, while the other two factors, demand and unfriendly relationship have a negative impact on workplace well-being. In addition, job burnout has a significant moderating effect on the relationship between job stress risk factor and well-being. Suggestions are provided for substitute educators’ well-being improvement.